Clinicopathological Characteristic and Prognostic Significance of Indonesian Triple Negative Breast Cancer - Irianiwati Widodo; Ery Kus Dwianingsih; Teguh Aryandono; Soeripto Soeripto (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Triple negative breast cancer (TNBC) is a breast cancer subtype with negative expressions of estrogen receptors (ER), progesterone receptors (PR) and Her-2 protein receptors. This subtype exhibits aggressive behavior and poor prognosis since it is unresponsive to hormonal and Her-2 targeted therapy. The identification of clinicopathological characteristics and their prognostic values will provide guidance in developing effective treatment. This study was performed to analyze the clinicopathological characteristics and prognostic significance in Indonesian TNBC.METHODS: Forty paraffin-embedded tissues of TNBC, stage I to IIIA, dating from 2008 to 2010 in Dr. Sardjito Hospital, were enrolled. Survival follow-up was done from January 2008 to June 2013. The samples were immunostained with ER, PR and Her-2 monoclonal antibodies to determine the TNBC subtypes. The clinicopathological characteristics were statistically analyzed. The survival was analyzed using the Kaplan Meier method. The Cox proportional hazards model was used for multivariate analysis.RESULTS: Mean age of TNBC patients was 51.42±11.72 years old, whereas the mean of tumor size was 5.4±2.92 cm. Lymph node metastasis was found in 70% of cases. Number of locally advanced samples (IIIA) was 37.5%, while moderate to high grade samples were 95%. Number of still alive patients at the end of the study was 55%. Number of patients that still alive up to the end of the study was 45.50%. Lymph node was an independent prognostic factor for survival of TNBC patients as positive status of lymph node increases the death risk to 6 times higher (p=0.02, RR=6.6). However, after being adjusted with age and stage, lymph node status was suggested as a modifier effect for the survival of TNBCs patients (RR=0.19).CONCLUSION: Indonesian TNBC patients were mostly found already with large tumor size, lymph node metastasis, high pathological grade and relatively young age. Lymph node status serves as a modifier effect for the survival of Indonesian TNBC.KEYWORDS: NBC, clinicopathological characteristics, prognostic significance